ANALYSIS OF THE CONTENT OF GEOGRAPHY TEACHING AND MODERN APPROACHES TO ITS IMPROVEMENT (Pedagogy of Higher and Secondary Education, 2009)
In article the general and didactic approaches to designing of the content of training are considered , necessity of complex consideration of the parties of complete pedagogical process, construction of the content of training of geography on the basis of harmonisation of substantial and remedial components is analyzed.